Bayesian Statistical Methods in Auditing. - Tracy, John A. (The Accounting Review, 1969)
Abstract The article discusses the advantages of using Bayesian statistical methods in audit tests. Bayesian methods accept the "subjective" nature of experience and other collateral evidence and blend it with the "objective" nature of actual sample test results. The auditor is constantly faced with a decision situation common to most economic problems-resource allocation to achieve optimal results. Bayesian statistics are decision oriented, concerned in particular with the economic consequences of making right or wrong decisions based on probabilities. The auditor invariably has a good deal of historical and current collateral audit evidence about the expected characteristics of audit test areas. The auditor should integrate this evidence into the statistical analysis of sample results. Bayesian statistics is the method that integrates such evidence in the form of a priori probabilities. The auditor thus gains the maximum value from the audit sample. The auditor is less likely to over-extend or under-extend audit procedures.